Durable goods inventories and the great moderation - James A. Kahn (Federal Reserve Bank of New York, 2008)
This paper revisits the hypothesis that changes in inventory management were an important contributor to volatility reductions during the Great Moderation. It documents how changes in inventory behavior contributed to the stabilization of the U.S. economy within the durable goods sector, in particular, and develops a model of inventory behavior that is consistent with the key facts about volatility decline in that sector. The model is calibrated to evidence from survey data showing that lead times for materials orders in manufacturing shrank after the early 1980s. Simulations of the model show large reductions in the volatility of output growth and more modest reductions in the volatility of sales growth. In addition, the model addresses concerns raised by a number of researchers who criticize the inventory literature's focus on finished goods inventories, given that stocks of works-in-process and materials are actually larger and more volatile that those of finished goods. The model adapts the stockout-avoidance concept to a production-to-order setting and shows that much of the intuition and results regarding production volatility still apply.
Keywords: D21; E20; N12; 330; Great Moderation; inventories; volatility